2005
DOI: 10.1159/000084778
|View full text |Cite
|
Sign up to set email alerts
|

High Distress in Parents Whose Children Undergo Predictive Testing for Long QT Syndrome

Abstract: Objectives: To assess the psychological effect of predictive testing in parents of children at risk for long QT syndrome (LQTS) in a prospective study.Methods: After their child was clinically screened by electrocardiography and blood was taken for DNA analysis, and shortly after delivery of the DNA test result, 36 parents completed measures of psychological distress. Results: 24 parents were informed that at least one of their children is a mutation carrier. Up to 50% of the parents of carrier children showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 60 publications
(40 reference statements)
0
26
0
Order By: Relevance
“…The risk status of their child apparently imposes a tangible instead of a hypothetical threat for these parents. We suggested earlier that the re-experiencing of events related to sudden or near deaths in the family may also explain this finding [Hendriks et al, 2005].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The risk status of their child apparently imposes a tangible instead of a hypothetical threat for these parents. We suggested earlier that the re-experiencing of events related to sudden or near deaths in the family may also explain this finding [Hendriks et al, 2005].…”
Section: Discussionmentioning
confidence: 71%
“…In an earlier study, we reported that no less than 50% of the parents who were informed that their child is a mutation carrier showed clinically relevant high levels of distress at the short term [Hendriks et al, 2005]. In view of this high figure, it was relevant to examine if our group of parents would react, as favorable in the long term as the parents mentioned in the other studies.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As in the adult population, high levels of distress and anxiety were observed in Ϸ50% of parents after disclosure of abnormal or uncertain ECG results in their children. 76 The level of anxiety was essentially unchanged after receiving a positive gene test result, and persisted at 18 months of follow-up. In contrast, negative gene test results lowered distress scores.…”
Section: Parental Influences and Perceptionsmentioning
confidence: 95%
“…Genetic counseling is inextricably connected to obtaining the molecular genetic testing, and the associated costs (also significant) should therefore be considered an inherent part of the process. In addition, as presymptomatic testing (ie, genetic testing and cardiologic evaluation) has significant psychological impact, 3,4 it cannot be emphasized enough that (cardio-) genetic testing requires a concerted action of dedicated cardiologists, clinical geneticists, and social workers. Furthermore, the mere fact that almost half of the patients referred to the Mayo Clinics for LQTS (genetic) testing did not have LQTS 5 emphasizes that these tests are best ordered/coordinated by dedicated "cardiogeneticists," be it either with a cardiological or genetic background.…”
Section: Article See Pmentioning
confidence: 99%